2015
DOI: 10.1097/md.0000000000001861
|View full text |Cite
|
Sign up to set email alerts
|

Modified Glasgow Prognostic Score is Associated With Risk of Recurrence in Bladder Cancer Patients After Radical Cystectomy

Abstract: Recently, many studies explored the role of inflammation parameters in the prognosis of urinary cancers, but the results were not consistent. The modified Glasgow Prognostic Score (mGPS), a systemic inflammation marker, is a prognostic marker in various types of cancers. The aim of the present study was to investigate the usefulness of the preoperative mGPS as predictor of recurrence-free (RFS), overall (OS), and cancer-specific (CSS) survivals in a large cohort of urothelial bladder cancer (UBC) patients.A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 25 publications
0
52
0
Order By: Relevance
“…The inflammation-based prognostic score such as Glasgow prognostic score,19 neutrophil-to-lymphocyte ratio,20 aspartate aminotransferase-to-platelet ratio,21 and platelet-to-lymphocyte ratio22 was proven to be independent prognostic parameters by previous studies. However, there are still some limitations for the use of these prognostic scores in patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammation-based prognostic score such as Glasgow prognostic score,19 neutrophil-to-lymphocyte ratio,20 aspartate aminotransferase-to-platelet ratio,21 and platelet-to-lymphocyte ratio22 was proven to be independent prognostic parameters by previous studies. However, there are still some limitations for the use of these prognostic scores in patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The modified Glasgow Prognostic Score (mGPS), a systemic inflammation marker, was found as a prognostic marker for recurrence in patients with urothelial bladder (22). On the other hand, bladder epithelium and bladder cancer cells express CD44 that binds glycosaminoglycans (GAG) such as chondroitin sulphate (CS).…”
Section: Discussionmentioning
confidence: 99%
“…A summary of six studies investigating the prognostic role of GPS/mGPS in UC is shown in Table . Four studies examined patients with bladder cancer, and two studies examined patients with upper tract UC.…”
Section: Serum Protein Markersmentioning
confidence: 99%
“…A summary of six studies investigating the prognostic role of GPS/mGPS in UC is shown in Table 6. [69][70][71][72][73][74] Four studies 71,73 Four studies showed a prognostic value of GPS/mGPS in relation to OS or RFS: increased GPS/mGPS was significantly associated with worse prognosis. Lucca et al evaluated the association between non-organ-confined disease and several SIR markers including NLR, PLR, MLR, PNI and GPS in patients who underwent radical cystectomy.…”
Section: Gps/mgps In Ucmentioning
confidence: 99%